2021
DOI: 10.3390/f12081020
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost Automatic Reconstruction of Tree Structure by AdQSM with Terrestrial Close-Range Photogrammetry

Abstract: The quantitative structure model (QSM) contains the branch geometry and attributes of the tree. AdQSM is a new, accurate, and detailed tree QSM. In this paper, an automatic modeling method based on AdQSM is developed, and a low-cost technical scheme of tree structure modeling is provided, so that AdQSM can be freely used by more people. First, we used two digital cameras to collect two-dimensional (2D) photos of trees and generated three-dimensional (3D) point clouds of plot and segmented individual tree from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…TreeQSM fits cylinders of each segment segmented from tree point clouds rather than depending on the tree skeleton, while AdQSM fits cylinders based on the extracted complete skeleton [42,48,64]. In several previously reported studies, comparable estimation accuracies between TreeQSM and AdQSM are observed for volume estimation in tropical forests [48] and for stem volume estimation using terrestrial close-range photogrammetry point clouds in a deciduous plantation [65].…”
Section: Accuracy Of Estimating Forest Structural Metrics Between Dif...mentioning
confidence: 77%
See 1 more Smart Citation
“…TreeQSM fits cylinders of each segment segmented from tree point clouds rather than depending on the tree skeleton, while AdQSM fits cylinders based on the extracted complete skeleton [42,48,64]. In several previously reported studies, comparable estimation accuracies between TreeQSM and AdQSM are observed for volume estimation in tropical forests [48] and for stem volume estimation using terrestrial close-range photogrammetry point clouds in a deciduous plantation [65].…”
Section: Accuracy Of Estimating Forest Structural Metrics Between Dif...mentioning
confidence: 77%
“…The results show that there are no apparent differences in tree height estimates using TreeQSM and AdQSM, regardless of ALS or DAP point clouds, at both plot and tree levels. The TreeQSM-and AdQSM-derived tree height estimates have been widely reported, and very good performance was achieved in deciduous species [48,65]. However, TreeQSM performed better than AdQSM based on ALS point clouds for estimating DBH, while the opposite was found for estimating crown area.…”
Section: Accuracy Of Estimating Forest Structural Metrics Between Dif...mentioning
confidence: 97%
“…Direct estimate of tree biomass from the TLS cloud can be assessed by means of estimating tree volume through QSM (quantitative structural modeling) assuming geometrical shapes (commonly cylinders) for both the stem and branches of the tree [34,65]. While this method seems optimal for estimating the biomass of adult or even extra mature trees [34,66,67], its application to short-rotation coppices is quite difficult since a single stool may share different small-sized shoots, and the dominant one is occluded by the lateral shoots, which makes difficult the correct definition of the main stem volume, where a large amount of biomass is accumulated. As an alternative, and conforming to the main innovation of our work, we do not aim to directly obtain estimates of stool biomass from TLS measurements, but we focus on obtaining easy-to-measure TLS-derived metrics to be included in the models for individual stool and plot biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Context domain knowledge was employed by Dong et al (2021), which uses the Pix4D photogrammetric suite to reconstruct tree structures; the approach is characterized as close range compared to aerial photogrammetry, although the imaging distance is several meters. The method further uses domain-specific knowledge (tree structure) to optimize the reconstruction of tree trunks and is not a generic photogrammetric method.…”
Section: Recent Adaptations and Variants Of Close-range Photogrammetrymentioning
confidence: 99%